Acute Toxicity of Water Soluble Fraction of Crude Oil to the Early Life Stages of the African Catfish (Clarias gariepinus): Crude Oil Toxicity to African Catfish - Izegaegbe, Joshua Idowu; Oloye, Femi Francis; Obuotor, Efere Martins; Olaleye, Victor Funso; Adeyeni, Stephen (Biological Sciences - PJSIR, 2014)